Composite aerogel, recoverable heat-storage phase-change composite material with photo-thermal conversion function and preparation method and application of recoverable heat-storage phase-change composite material
Patent Information
- Application Number
- CN202380064060.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-08
- Publication Date
- 2025-04-11
AI Technical Summary
Existing organic phase change materials are prone to leakage when directly used as energy storage materials and are difficult to recycle, leading to environmental pollution and resource waste, and lack effective photothermal conversion functions to utilize solar energy.
Composite aerogels are prepared by mixing maleimide-based copolymers and graphene oxide as carriers of phase change materials. The ammonia water is recycled and the photothermal conversion function is realized to reduce the leakage of phase change materials.
It achieves leakage prevention and recycling of phase change materials, has good photothermal conversion performance and heat storage performance, supports environmentally friendly use of solar energy, and reduces the environmental impact of the material.
Smart Images

Figure CN119816551A_ABST
Abstract
Description
Composite aerogel, recyclable heat storage phase change composite material with photothermal conversion function, preparation method and application Technical Field
[0001] The present invention relates to the field of phase change materials, and in particular to a composite aerogel, a recyclable heat storage phase change composite material with a light-to-heat conversion function, and a preparation method and application thereof. Background Art
[0002] With the rapid increase in energy consumption and greenhouse gas emissions, the environmentally friendly utilization of renewable energy sources such as solar energy and waste heat is extremely attractive. Because solar energy varies over time and space, the mismatch between energy supply and demand makes the efficient storage of this energy a critical issue. Latent heat energy storage systems based on organic phase change materials (PCMs) offer large energy storage capacity, a nearly constant phase change temperature, and reversible storage and release of thermal energy. PCMs can bridge the significant gap between rapidly growing energy demand and limited fossil resource reserves. Consequently, PCMs are currently widely used in air conditioning systems, building materials, solar energy storage, waste heat recovery, and various electronic products. Organic PCMs, with their advantages of stable performance, low supercooling, and lack of phase separation, are the most widely studied PCMs. These materials primarily include paraffin wax, fatty acids, fatty alcohols, and other organic compounds. However, direct use of organic PCMs as energy storage materials carries the risk of leakage, making encapsulation of these materials essential to prevent leakage. Furthermore, reprocessability and recyclability are crucial considerations to avoid environmental pollution and resource waste.
[0003] Therefore, if a material with photothermal conversion performance is provided and combined with a phase change material to obtain a recyclable cold storage phase change composite material with good photothermal conversion performance, low phase change material leakage and recyclability, a major breakthrough will be achieved in this field.
[0004] Summary of the Invention
[0005] In response to the technical problems existing in the prior art, the purpose of the present invention is to provide a composite aerogel, a recyclable heat storage phase change composite material with photothermal conversion function, and a preparation method and application. The composite aerogel can be used as a carrier to load a phase change material to obtain a recyclable heat storage phase change composite material with photothermal conversion function, and can also be recycled in a simple and environmentally friendly manner; the recyclable heat storage phase change composite material with photothermal conversion function not only has the photothermal conversion function, but also has low phase change material leakage and can be recycled, truly realizing the utilization and effective storage of solar energy in an environmentally friendly manner.
[0006] The inventors of the present invention have discovered that maleimide-based copolymers (polymers containing maleic anhydride groups and maleimide groups) can be prepared through low-cost copolymers and can be recycled through ammonia water. In view of the existing technology, the applicants of the present invention have discovered in their research that by mixing such copolymers with graphene oxide and a reducing agent, a composite aerogel of maleimide-based copolymers and reduced graphene oxide can be prepared; preferably, the aerogel is quickly and efficiently reduced by microwaves to obtain a water-resistant maleimide-based copolymer-graphene composite aerogel. The composite aerogel can be used as a carrier of a phase change material, can be used to prevent leakage of the phase change material, and can be recovered under the action of ammonia water to obtain graphene, phase change material and polymer respectively. In summary, the present invention is intended to achieve leakage prevention and recovery of phase change materials with photothermal conversion function, and provide a composite aerogel suitable for a phase change material carrier, as well as a recyclable heat storage phase change composite material with photothermal conversion function and its preparation method and application.
[0007] The first aspect of the present invention provides a composite aerogel comprising a polymer and graphene, wherein the polymer contains structural units containing maleic anhydride groups and structural units containing maleimide groups. This composite aerogel can be used as a carrier and, when combined with a phase change material, to produce a recyclable heat storage phase change composite material with photothermal conversion capabilities. The composite aerogel can also be recycled in a simple and environmentally friendly manner.
[0008] In a preferred embodiment of the present invention, the Raman spectrum of the composite aerogel surface is D / I G The average value is equal to or less than 1.2, preferably equal to or less than 0.9, and more preferably equal to or less than 0.85.
[0009] According to the present invention, the mass ratio of graphene to polymer can be selected within a wide range. In a preferred embodiment of the present invention, the mass ratio of graphene to polymer is (1:20)-(10:1), preferably (1:10)-(6:1), and more preferably (1:5)-(1:1), that is, 1:(1-5). For example, the ratio can be 1 to 1, 2, 3, 4, 5, or any two values or any interval between any two values.
[0010] According to the present invention, the polymer in the composite aerogel can be dissolved in ammonia water at 0-150° C. to form a polymer aqueous solution.
[0011] In a preferred embodiment of the present invention, the graphene in the raw materials for preparing the composite aerogel of the present invention is obtained by reducing graphene oxide. The graphene oxide is first pre-reduced with a reducing agent and then reduced by microwaves. That is, the graphene is obtained by reducing the graphene oxide. Preferably, the graphene oxide is first pre-reduced with a reducing agent and then reduced by microwaves.
[0012] According to the present invention, the reducing agent can be selected from a wide range. In a preferred embodiment of the present invention, the reducing agent is selected from at least one of ascorbic acid, gallic acid, sodium borohydride, and amino acids.
[0013] According to the present invention, a maleic anhydride group refers to The maleimide group refers to
[0014] According to the invention, the polymers are carbon chain polymers in which the heteroatoms O and N are present in side groups.
[0015] In a preferred embodiment of the present invention, based on the total molar amount of the structural units containing maleic anhydride groups and the structural units containing maleimide groups as 100%, the molar ratio of the structural units containing maleimide groups in the polymer is 5%-70%, preferably 10%-60%; more preferably 20%-50%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, and any two values or any interval between any two values.
[0016] According to the present invention, the polymer can be selected from a wide range. In a preferred embodiment of the present invention, the polymer is derived from a polymer raw material containing one or more structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, or maleamic acid and ammonium salt groups; that is, the maleic anhydride groups and maleimide groups in the above-mentioned polymer aerogel are derived from at least one of the maleic anhydride groups, maleimide groups, maleic acid and ammonium salt groups, or maleamic acid and ammonium salt groups in the polymer raw material.
[0017] The maleic anhydride group refers to The maleimide group refers to Maleic acid and ammonium salt groups, maleamic acid and ammonium salt groups refer to Wherein M is the same or different and each is hydroxyl, amino or ammonium (O-NH4).
[0018] According to the invention, the polymers are carbon chain polymers in which the heteroatoms O and N are present in side groups.
[0019] In the present invention, the polymer raw materials include, but are not limited to, copolymers of one or more monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salts, or maleamic acid and ammonium salts, and olefin monomers. For example, the present invention can also be achieved when the polymer raw materials are styrene-maleic anhydride-vinyl silicone oil copolymers. Copolymers of one or more monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salts, or maleamic acid and ammonium salts, and olefin monomers have lower raw material costs.
[0020] Preferably, the polymer raw material is a copolymer of one or more polymerized monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt, and an olefin monomer; more preferably, the olefin monomer is at least one of α-methylstyrene, styrene, and isobutylene; more preferably, the polymer raw material is an alternating copolymer of one or more polymerized monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt, and one of α-methylstyrene, styrene, and isobutylene.
[0021] For example, the polymer raw material in the present invention includes but is not limited to at least one of styrene maleic anhydride copolymer and maleic anhydride isobutylene copolymer. Preferably, the polymer raw material is styrene maleic anhydride copolymer.
[0022] In a preferred embodiment of the present invention, the composite aerogel can be dissolved in ammonia water at 0-150° C. to form a polymer aqueous solution. Based on this, the polymer aerogel of the present invention can be recycled conveniently and environmentally friendly.
[0023] According to the present invention, the polymer in the composite aerogel has good heat resistance and still has good heat resistance after recycling, and is very suitable for photothermal conversion heat storage carrier.
[0024] In a preferred embodiment of the present invention, the composite aerogel is prepared by reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt groups with aqueous ammonia in a sealed condition, and then mixing the polymer raw material with graphene oxide and a reducing agent, followed by pre-freezing, freeze-drying, dehydration and deamination, and reduction treatment.
[0025] The second aspect of the present invention provides a method for preparing the composite aerogel described in the first aspect, comprising reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia in a sealed environment, then mixing the polymer raw material with graphene oxide and a reducing agent, and then subjecting the mixture to pre-freezing, freeze-drying, dehydration and deamination, and reduction treatment to obtain the composite aerogel.
[0026] No cross-linking agent is added in the composite aerogel preparation method of the present invention.
[0027] In a preferred embodiment of the present invention, the preparation method comprises the following steps:
[0028] (1) reacting the polymer raw material with ammonia water in a sealed environment to obtain a polymer aqueous solution;
[0029] (2) mixing the polymer aqueous solution obtained in step (1) with graphene oxide and a reducing agent to obtain a mixed solution, then pre-freezing the mixed solution, and then freeze-drying it to obtain a composite polymer;
[0030] (3) The composite polymer obtained in step (2) is subjected to heat treatment for dehydration and deamination, and then subjected to microwave irradiation for reduction treatment to obtain the maleimide copolymer graphene composite aerogel.
[0031] According to the present invention, the amount of polymer raw material and ammonia water in step (1) can be selected within a wide range. In a preferred embodiment of the present invention, based on the total mass of the reaction system as 100%, the mass fraction of the polymer raw material is 0.1%-30%, preferably 0.5%-10%, more preferably 1%-5%. Based on the mass of ammonia in ammonia water, the mass fraction of ammonia in the raw material is 0.001%-30%, preferably 0.01%-10%, more preferably 0.1%-1%, and the remaining components are water.
[0032] According to the present invention, the reaction conditions in step (1) can be selected within a wide range. In a preferred embodiment of the present invention, the reaction conditions include: a reaction temperature of 0-200° C., preferably 50-150° C., more preferably 80-100° C., and / or a reaction time of 0.01-100 h, preferably 0.5-10 h, more preferably 1-5 h. The reaction pressure is not particularly limited, but is preferably carried out under normal pressure.
[0033] According to the present invention, the conditions in step (2) can be selected within a wide range. In a preferred embodiment of the present invention, in step (2): the graphene oxide is derived from a dispersion containing graphene oxide, and the concentration of graphene oxide in the dispersion (that is, the mass ratio of graphene oxide to water) is 1-100 mg / mL, preferably 3-30 mg / mL, and more preferably 5-20 mg / mL.
[0034] According to the present invention, the reducing agent can be selected from a wide range. In a preferred embodiment of the present invention, the reducing agent is selected from at least one of ascorbic acid, gallic acid, sodium borohydride, and amino acids.
[0035] According to the present invention, the mass ratio of the reducing agent to graphene oxide can be selected within a wide range. In a preferred embodiment of the present invention, the mass ratio of the reducing agent to graphene oxide is 1:(0.1-20), preferably 1:(1-3), for example, it can be 1 to 1, 1.5, 2, 2.5, 3, and the ratio of any two values or any interval between any two values.
[0036] According to the present invention, the polymer aerogel in the present invention can be an anisotropic aerogel or an isotropic aerogel.
[0037] The difference between anisotropic aerogels and isotropic aerogels lies in their pore structures. The pore structure of anisotropic aerogels exhibits long-range order, primarily due to the directional growth of ice crystals during the pre-freezing stage, which expel impurities during growth and form pore walls. Therefore, anisotropic aerogels can be produced by varying the temperature of the unidirectional cooling source during pre-freezing. There are multiple options for implementing the unidirectional cooling source temperature, including but not limited to using liquid nitrogen as the low-temperature cooling source during pre-freezing, placing a mold containing a mixture of a polymer aqueous solution, graphene oxide, and a reducing agent on a copper column immersed in liquid nitrogen, and allowing ice crystals to grow upward from the bottom of the mold.
[0038] Anisotropic aerogels have different pore structures, different axial and radial thermal conductivities, and different material and sound transmission rates. Anisotropic and isotropic aerogels can be selected based on different applications. For example, when encapsulating phase change materials in the present invention, the inventors discovered that using the preferred anisotropic aerogel significantly reduced leakage, regardless of the orientation of the anisotropic aerogel.
[0039] According to the present invention, the cooling source temperatures of the mixed liquid in all directions during pre-freezing are the same or different. In a preferred embodiment of the present invention, the cooling source temperatures of the mixed liquid in all directions during pre-freezing are different. Preferably, the cooling source temperature of the mixed liquid (i.e., the aqueous solution of the copolymer obtained after the amination reaction, the graphene, and the reducing agent) in one direction during pre-freezing is different. In this preferred embodiment, leakage of the phase change material is reduced.
[0040] Preferably, different unidirectional cooling source temperatures during pre-freezing can produce anisotropic aerogels. The unidirectional cooling source temperature can be implemented in a variety of ways, including but not limited to using liquid nitrogen as the low-temperature cooling source during pre-freezing, placing the mold on a copper column immersed in liquid nitrogen, and allowing ice crystals to grow upward from the bottom of the mold.
[0041] Specifically, the pre-freezing conditions can be conventional temperature conditions in the art, and the present invention has no particular limitation, as long as the mixed solution of the polymer aqueous solution, graphene oxide, and reducing agent in step (2) is frozen into ice.
[0042] According to the present invention, the freeze-drying conditions can be selected within a wide range, and the present invention is not particularly limited. In a preferred embodiment of the present invention, the freeze-drying conditions include: a temperature of below (-10)°C, for example, below (-20)°C, or below (-30)°C, and / or a vacuum degree of below 1000Pa, for example, below 100Pa, or below 10Pa.
[0043] The freeze drying process can adopt various freeze drying equipment in the prior art, such as freeze dryer, freeze spray dryer, industrial freeze dryer, etc.
[0044] According to the present invention, the conditions in step (3) can be selected within a wide range. In a preferred embodiment of the present invention, in step (3): the heat treatment conditions include: a temperature of 100-300°C, preferably 120-220°C, more preferably 160-200°C; and a heat treatment time of 0.1-10 hours, preferably 0.5-3 hours, more preferably 1-2 hours.
[0045] According to the present invention, the microwave irradiation conditions can be selected within a wide range. In a preferred embodiment of the present invention, the microwave irradiation power is 500-2000 W; the microwave irradiation time is 1-10 s, preferably 2-7 s, and more preferably 3-5 s.
[0046] According to the present invention, the polymer raw material can be selected from a wide range. In a preferred embodiment of the present invention, the polymer raw material can react with ammonia water to obtain a water-soluble polymer.
[0047] In a preferred embodiment of the present invention, the polymer raw material is a polymer containing one or more structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups; preferably, the polymer raw material is a copolymer of one or more polymerization monomers including maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt and an olefin monomer; more preferably, the olefin monomer includes at least one of α-methylstyrene, styrene, and isobutylene; as an example, the polymer raw material includes but is not limited to at least one of styrene maleic anhydride copolymer and maleic anhydride isobutylene copolymer.
[0048] The polymer raw materials mentioned above are all polymers disclosed in the prior art, and can be commercially available from the prior art, or prepared according to the methods disclosed in the prior art.
[0049] In the present invention, there is no particular limitation on the material of the sealed container, which may be made of metal, non-metal, polymer or other materials.
[0050] The “and / or” involved in the present invention means that the two conditions before and after “and / or” can be selected one by one, or the two conditions can exist at the same time.
[0051] The third aspect of the present invention is to provide a recyclable heat storage phase change composite material, comprising a composite aerogel and a phase change material loaded in the composite aerogel; the composite aerogel is the composite aerogel described in the first aspect or the composite aerogel prepared by the preparation method described in the second aspect.
[0052] According to the present invention, the mass ratio of the composite aerogel to the phase change material can be selected within a wide range. In a preferred embodiment of the present invention, the mass ratio of the composite aerogel to the phase change material is 1:(0.05-50), for example, it can be 1 to 0.05, 0.1, 0.5, 1, 5, 10, 20, 30, 40, 50, or the ratio of any two values or any interval between any two values.
[0053] According to the present invention, the phase change material can be selected from a wide range. The phase change material is preferably an organic phase change material, preferably a heat storage phase change material; including but not limited to water-soluble phase change materials and / or water-insoluble phase change materials, more preferably at least one of polyethylene glycol, lauric acid, stearyl alcohol, and paraffin.
[0054] In a preferred embodiment of the present invention, under the temperature condition where the phase change material is liquid, the leakage amount of the phase change material in the recyclable heat storage phase change composite material is less than 10 wt%, preferably less than 5 wt%, and more preferably less than 2 wt%.
[0055] The present invention also provides a method for recovering composite aerogels or recyclable heat-storing phase-change composite materials. The method comprises mixing the composite aerogels and / or recyclable heat-storing phase-change composite materials with ammonia water in a closed environment until an aqueous solution containing the recovered polymer is obtained, and then removing insoluble matter (graphene, phase-change material) to obtain an aqueous solution of the recovered polymer. This aerogel recovery method does not require the introduction of organic solvents or high-temperature, high-pressure stirring. It only requires a certain concentration of ammonia water, preferably maintained below 100 degrees Celsius, enabling rapid and efficient recovery. This method has low energy consumption, low pollution, and high efficiency. The recovered polymer solution can be reused in the preparation of polymer aerogels.
[0056] According to the present invention, the conditions for the mixed reaction in the recovery method can be selected within a wide range. In a preferred embodiment of the present invention, the mixed reaction temperature is 0-200° C., preferably 50-150° C., more preferably 80-100° C., and / or the mixed reaction time is 0.01-100 h, preferably 0.5-10 h, more preferably 1-5 h. The reaction pressure is not particularly limited, but is preferably carried out under normal pressure.
[0057] In a preferred embodiment of the present invention, the recovery method further comprises reusing the aqueous solution of the recovered polymer, for example, continuing step (2) and subsequent steps in the preparation method described in the second aspect of the present invention to re-prepare the composite aerogel.
[0058] The fourth aspect of the present invention is to provide a method for preparing the recyclable heat storage phase change composite material according to the third aspect, comprising loading the phase change material in the composite aerogel.
[0059] According to the present invention, the method for preparing the recyclable heat storage phase change composite material comprises: using the preparation method described in the second aspect to obtain a composite aerogel; and loading the phase change material into the composite aerogel. The loading method may be any of the various loading methods known in the art. Specifically, the phase change material may be molten and then adsorbed (encapsulated) and / or infiltrated into the composite aerogel.
[0060] According to the present invention, the type and ratio of the phase change material can be selected from a wide range, preferably the type and ratio of the phase change material described in the third aspect of the present invention.
[0061] The fifth aspect of the present invention is to provide an application of the recyclable heat storage phase change composite material described in the fourth aspect in the fields of building energy conservation, air-conditioning systems, waste heat utilization, and solar energy storage.
[0062] Through the above technical solution, the present invention provides a composite aerogel, a recyclable heat storage phase change composite material with photothermal conversion function, and its preparation method and application. Compared with the existing technology, the present invention has the following advantages:
[0063] The composite aerogel in this invention serves as a carrier, and the graphene within it imparts photothermal conversion capabilities to the phase-change material. The graphene-containing aerogel phase-change composite material can heat to above 70°C within 30 minutes under sunlight and maintain a temperature above 50°C for extended periods, demonstrating excellent photothermal conversion and heat storage properties. Combined with the heat storage properties of the phase-change material, the recyclable heat-storing phase-change composite material with photothermal conversion capabilities in this invention can achieve efficient utilization of solar energy.
[0064] The composite aerogel and the recyclable heat storage phase change composite material with light-to-heat conversion function in the present invention can be recycled in a green and environmentally friendly way;
[0065] The polymers in the composite aerogel and the recycled polymers have good heat resistance. At the same time, the porous structure of the composite aerogel makes the leakage of the phase change material low. All of the above provide stability guarantees for photothermal conversion and heat storage.
[0066] In summary, the recyclable heat storage phase change composite material with photothermal conversion function in the present invention not only has photothermal conversion function, but also has good heat storage performance. In addition, the phase change material has low leakage and the overall material can be recycled, which truly realizes the environmentally friendly use of solar energy and effective storage, and has extremely high application value in the environmentally friendly use of clean energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] FIG1 is a DSC curve and glass transition temperature Tg of the maleimide-based aerogel in Comparative Example 1 and the polymer aerogel recovered in Example 4;
[0068] FIG2 is a thermogravimetric curve of the maleimide-based aerogel in Comparative Example 1 and the polymer aerogel recovered in Example 4;
[0069] The test results of Figures 1 and 2 show that maleimide-based aerogels have good heat resistance, with a glass transition temperature of around 250°C and a decomposition temperature of around 300°C. The heat resistance of aerogels prepared from recycled polymers is higher than that before recycling, proving that the polymers have good heat resistance before and after aerogel recycling, and the recycling process is green and environmentally friendly.
[0070] FIG3 is a temperature curve of the phase change materials of Example 2 and Example 5 under one sunlight intensity and after the sunlight is removed.
[0071] The test results in Figure 3 show that graphene gives the phase change material the function of photothermal conversion. The aerogel phase change composite material containing graphene can be heated to above 70°C within 30 minutes under simulated sunlight, and can maintain a temperature above 50°C for a long time. It has good photothermal conversion performance and heat storage performance, and can achieve efficient utilization of solar energy.
[0072] Figure 4 shows the maleimide-based copolymer graphene aerogel phase change composite material (a) obtained in Example 2 and the recovered graphene phase change composite material (b) and polymer aerogel (c), which are described in Example 4. It can be seen that the materials in the recyclable heat storage phase change composite material with light-to-heat conversion function of the present invention can be recycled and reused separately. DETAILED DESCRIPTION
[0073] The present invention will be described in detail below with reference to specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made by those skilled in the art to the present invention based on the contents of the present invention still fall within the scope of protection of the present invention.
[0074] The present invention will be further described below with reference to the embodiments; however, the present invention is not limited to these embodiments.
[0075] The experimental data in the examples were measured using the following instruments and measurement methods:
[0076] 1. Raman spectrum ID / IG test method of aerogel:
[0077] The test was performed using a Lab RAM HR800 Raman spectrometer from HORIBA JOBIN YVON. The curves were processed using the machine's built-in software to obtain the ID and IG values.
[0078] 2. Thermal stability test method of aerogel:
[0079] The thermal stability of the samples was determined by thermogravimetric analysis (TGA, Mettler Toledo, Switzerland). 5 mg of aerogel was tested under a nitrogen flow at a heating rate of 20°C / min from 50°C to 550°C.
[0080] 3. Aerogel glass transition temperature test method:
[0081] The glass transition temperature of the samples was measured using a Perkin-Elmer pyris -1 Differential scanning calorimetry (DSC) was performed using indium and zinc standards for calibration. A 5-6 mg sample was injected from a rod and heated from 150°C to 300°C under a nitrogen stream, held at 300°C for 3 minutes. The sample was then cooled to 150°C for 1 minute and then heated again to 300°C. All heating and cooling processes were programmed at a rate of 10°C / min. The glass transition temperature (Tg) was determined from the relevant peaks in the DSC curve.
[0082] 4. Test method for temperature change curve of phase change material simulating sunlight:
[0083] The phase change material was cut into 3cm*3cm*0.3cm sheets as test samples. The solar simulator Sirius-SS300A-D produced by Beijing Zhuoli Hanguang Instrument Co., Ltd. was used to simulate sunlight at 20 degrees Celsius. The sample was placed in an uncovered polystyrene foam box and the temperature change of the phase change composite material was monitored by thermocouples throughout the process. First, under a light intensity of 100mW / cm 2 After irradiating for about 34 minutes at the intensity of one sun, the simulated light source was turned off.
[0084] 5. Phase change material leakage test method:
[0085] Take 15g of the sample obtained in the embodiment, take filter paper and place it on a 120℃ heating table, leave the sample on the filter paper for 10 minutes, remove the sample, and weigh the sample to obtain m (g). The leakage amount is: m / 15*100wt%. If the sample is completely melted and cannot be removed, the leakage amount is 100wt%.
[0086] 6. Test method for phase change temperature:
[0087] The thermal properties of aerogels and phase-change materials were measured using differential scanning calorimetry (DSC) using a Perkin-Elmer pyris-1 calibrated with indium and zinc standards. For aerogels, samples were heated from 20°C to 150°C under a nitrogen flow, holding at 20°C and 150°C for 5 min each. For phase-change materials, samples were heated from 50°C to 300°C under a nitrogen flow, holding at 50°C and 300°C for 5 min each. All heating and cooling processes were programmed at a rate of 20°C / min. The latent heats of melting, ΔHm, and solidification, ΔHf, as well as the melting and solidification temperatures, Tm and Tf, were determined from the relevant peaks in the DSC curves.
[0088] The raw materials used in the examples are described in Table 1.
[0089] Table I
[0090] Preparation Example 1
[0091] In the present embodiment, the polymer was prepared by placing 500 ml of isoamyl acetate in a 1000 ml three-necked flask and purging it with nitrogen for 30 minutes to remove oxygen. Then, 24.5 g of maleic anhydride and 26 g of styrene were added to the flask. After complete dissolution, 0.4 g of azobisisobutyronitrile was added. The water bath temperature was raised to 70°C and the reaction was allowed to proceed for 7 hours. After the reaction, the mixture was centrifuged at 10,000 rpm for 10 minutes, the supernatant removed, and 500 ml of methanol added. The mixture was stirred for 0.5 hours, centrifuged, and the supernatant removed. This process was repeated twice, followed by vacuum drying at 140°C for 24 hours to obtain a styrene-maleic anhydride copolymer.
[0092] Example 1
[0093] Take 93.2g of water and add it to a covered glass bottle. Then add 2.8g of 25% ammonia water and 4g of maleic anhydride-styrene copolymer. After tightening the cap of the glass bottle, place it in an oven and maintain it at 95°C. After 4 hours, take it out to obtain a uniform 4% mass fraction polymer solution.
[0094] To a glass bottle, add 100g of a 20mg / ml aqueous solution of graphene oxide, followed by 4g of ascorbic acid. Magnetic stirring is applied at 1000 rpm for 5 minutes. Once thoroughly mixed, the mixture is quickly poured into a cylindrical mold with a copper bottom and a polytetrafluoroethylene wall. The mold is then placed on a copper cylinder in a liquid nitrogen bath. After pre-freezing (i.e., freezing the mixture to ice), the mixture is placed in a freeze dryer (temperature below -30°C and pressure below 10 Pa) and freeze-dried for 72 hours to yield an anisotropic, water-soluble GO / SMI composite aerogel.
[0095] The aerogel was then placed in a polytetrafluoroethylene liner filled with nitrogen and heat-treated in a constant temperature box at 180°C for 2 hours. The sample was taken out and placed in a sealed quartz jar filled with nitrogen, and microwave-treated (irradiation power of 800 W) for 3 seconds to obtain a maleimide styrene copolymer graphene composite aerogel (i.e., the composite aerogel in the present invention).
[0096] Example 2
[0097] A maleimide graphene composite aerogel was prepared according to the method in Example 1, and 0.2 g of the maleimide graphene composite aerogel was placed in a polytetrafluoroethylene beaker containing 20 g of sliced paraffin wax. The container was placed in a vacuum oven and maintained at 100°C for 2 hours, and the molten paraffin wax penetrated into the maleimide graphene composite aerogel, thereby obtaining an aerogel phase change composite material; the aerogel phase change composite material was taken out from the container, and then the excess phase change material on the surface of the aerogel phase change composite material was wiped off. After standing at room temperature for 2 hours, the maleimide copolymer graphene aerogel phase change composite material (about 10 g of adsorbed paraffin wax) was obtained after weighing.
[0098] Example 3
[0099] The phase change material in Example 2 was replaced by octadecyl alcohol (purchased from Aladdin) from paraffin, and the rest of the experiments were consistent with Example 2.
[0100] The recovery effect of the obtained phase change composite material is close to that of Example 2.
[0101] Example 4
[0102] The phase change composite material sample obtained in Example 2 was ground into powder, 5g of powder was taken and placed in a glass bottle with a lid, and then 0.2g of 25% ammonia water and 30ml of water were added, heated to 95°C and maintained under magnetic stirring at 1000r / min for 1h, then filtered while hot (a in Figure 4), the filtrate was heated and concentrated to about 5ml, placed in a mold refrigerator for pre-freezing, and then placed in a freeze dryer for freeze drying (temperature below -30°C and pressure below 10Pa) to obtain a recovered polymer aerogel (c in Figure 4), the filter cake was naturally dried and placed in a small beaker, heated to 100°C and melted and maintained for 1h, and then cooled to obtain a high-value-added product graphene phase change composite material, which was cut and shaped as needed (b in Figure 4). It can be seen that the materials in the recyclable heat storage phase change composite material with light-to-heat conversion function in the present invention can be recycled and reused separately.
[0103] Example 5
[0104] Take 91.5g of water and add it to a covered glass bottle. Then add 3.5g of 25% ammonia water and 5g of maleic anhydride-styrene copolymer. After tightening the cap of the glass bottle, place it in an oven and maintain it at 95°C. After 4 hours, take it out to obtain a uniform 5% mass fraction polymer solution.
[0105] The polymer solution was poured into 6 molds, with 15 ml of the solution poured into each mold. The molds were then placed in a -30°C refrigerator and frozen for 2 hours. The frozen samples were transferred to a freeze dryer and freeze-dried (below -30°C, below 10Pa) for 72 hours. The resulting water-soluble polymer aerogel was then taken out. The water-soluble polymer aerogel was placed in a constant temperature container and heat treated at 180°C to dehydrate and deaminize to obtain a maleimide-based aerogel.
[0106] 0.5 g of maleimide-based polymer aerogel was placed in a 30 ml polytetrafluoroethylene beaker containing 20 g of sliced paraffin wax, and the container was placed in a vacuum oven and maintained at 100°C for 2 hours to obtain an aerogel phase change composite material; the aerogel phase change composite material was taken out of the container, and then the excess phase change material on the surface of the aerogel phase change composite material was wiped off. After being placed at room temperature for 2 hours, the maleimide-based copolymer aerogel phase change composite material (about 7 g of adsorbed paraffin wax) was weighed.
[0107] Example 6
[0108] The microwave treatment time in Example 1 was changed to 1 s, and the other preparation steps were the same as in Example 1.
[0109] Example 7
[0110] Take 93.2g of water and add it to a covered glass bottle. Then add 2.8g of 25% ammonia water and 4g of maleic anhydride-styrene copolymer. After tightening the cap of the glass bottle, place it in an oven and maintain it at 95°C. After four hours, take it out to obtain a uniform 4% mass fraction polymer solution.
[0111] To a glass bottle, add 100g of a 20mg / ml graphene oxide aqueous solution, followed by 4g of ascorbic acid. Stir magnetically at 1000 rpm for 5 minutes. Once thoroughly mixed, pour the mixture into a cylindrical mold with a copper bottom and a polytetrafluoroethylene wall. Place the mold on a copper cylinder in a liquid nitrogen bath. After pre-freezing, freeze-dry the mixture in a freeze dryer (below -30°C, below 10 Pa) for 72 hours to obtain an anisotropic, water-soluble GO / SMI composite aerogel.
[0112] The aerogel was then placed in a polytetrafluoroethylene liner filled with nitrogen and heat-treated in a constant temperature box at 180°C for 2 hours. The sample was taken out and placed in a sealed quartz jar filled with nitrogen, and microwave-treated (irradiation power of 800 W) for 5 seconds to obtain a maleimide styrene copolymer graphene composite aerogel.
[0113] Example 8
[0114] Take 93.2g of water and add it to a covered glass bottle. Then add 2.8g of 25% ammonia water and 4g of maleic anhydride-styrene copolymer. After tightening the cap of the glass bottle, place it in an oven and maintain it at 95°C. After four hours, take it out to obtain a uniform 4% mass fraction polymer solution.
[0115] To a glass bottle, add 100g of a 20mg / ml graphene oxide aqueous solution, followed by 4g of ascorbic acid. Stir magnetically at 1000 rpm for 5 minutes. Once thoroughly mixed, pour the mixture into a cylindrical mold with a copper bottom and a polytetrafluoroethylene wall. Place the mold on a copper cylinder in a liquid nitrogen bath. After pre-freezing, freeze-dry the mixture in a freeze dryer (below -30°C, below 10 Pa) for 72 hours to obtain an anisotropic, water-soluble GO / SMI composite aerogel.
[0116] The aerogel was then placed in a polytetrafluoroethylene liner filled with nitrogen and heat-treated in a constant temperature box at 180°C for 2 hours. The sample was taken out and placed in a sealed quartz jar filled with nitrogen, and microwave-treated (irradiation power of 800 W) for 7 seconds to obtain a maleimide styrene copolymer graphene composite aerogel.
[0117] Example 9
[0118] Take a reactor with a polytetrafluoroethylene liner, add 20.5g of water, then add 4g of 25% ammonia water and 0.5g of maleic anhydride-styrene copolymer, put the reactor into an oven and maintain it at 150°C. After 10 hours, take it out to obtain a uniform polymer solution.
[0119] 75g of a 40mg / ml graphene oxide aqueous solution was added to a reactor, followed by 3g of ascorbic acid. The mixture was magnetically stirred at 1000 rpm for 5 minutes. Once thoroughly mixed, it was quickly poured into a cylindrical mold with a copper bottom and a polytetrafluoroethylene wall. The mold was then placed on a copper cylinder in a liquid nitrogen bath. After pre-freezing, the mold was placed in a freeze dryer (below -30°C, below 10 Pa) and freeze-dried for 72 hours to obtain an anisotropic, water-soluble GO / SMI composite aerogel.
[0120] The aerogel was then placed in a polytetrafluoroethylene liner filled with nitrogen and heat-treated in a constant temperature box at 200°C for 2 hours. The sample was taken out and placed in a sealed quartz jar filled with nitrogen, and microwave-treated (irradiation power of 500 W) for 3 seconds to obtain a maleimide styrene copolymer graphene composite aerogel.
[0121] 0.2 g of maleimide-based polymer aerogel was placed in a 30 ml polytetrafluoroethylene beaker containing 20 g of sliced paraffin wax, and the container was placed in a vacuum oven and maintained at 100°C for 2 hours to obtain an aerogel phase change composite material; the aerogel phase change composite material was taken out of the container, and then the excess phase change material on the surface of the aerogel phase change composite material was wiped off. After being placed at room temperature for 2 hours, a copolymer graphene aerogel phase change composite material (about 4 g of paraffin wax was adsorbed) was obtained.
[0122] Example 10
[0123] Add 91.5 g of water to a covered glass bottle, then add 3.5 g of 25% ammonia water and 5 g of maleic anhydride-styrene copolymer. After tightening the glass bottle cap, place it in an oven and maintain it at 95°C. After 4 hours, take it out to obtain a uniform 5% mass fraction polymer solution, and dry it at room temperature to obtain a polymer containing maleamic acid and ammonium maleate groups.
[0124] The obtained polymer was placed in a glass bottle with a lid, 41.5 g of water was added, and then 0.04 g of 25% ammonia water was added. The lid of the glass bottle was tightened and placed in an oven maintained at 20° C. After 0.5 hours, a uniform polymer solution was obtained.
[0125] To a glass bottle, add 50g of a 6mg / ml graphene oxide aqueous solution and 0.9g of ascorbic acid. Stir magnetically at 1000 rpm for 5 minutes. Once thoroughly mixed, pour the mixture into a cylindrical mold with a copper bottom and a polytetrafluoroethylene wall. Place the mold on a copper cylinder in a liquid nitrogen bath. After pre-freezing, freeze-dry the mixture in a freeze dryer (below -30°C, below 10 Pa) for 72 hours to obtain an anisotropic, water-soluble GO / SMI composite aerogel.
[0126] The aerogel was then placed in a polytetrafluoroethylene liner filled with nitrogen and heat-treated in a constant temperature box at 130°C for 2 hours. The sample was taken out and placed in a sealed quartz jar filled with nitrogen, and microwave-treated (irradiation power of 2000 W) for 3 seconds to obtain a maleimide styrene copolymer graphene composite aerogel.
[0127] 0.2 g of maleimide-based polymer aerogel was placed in a 30 ml polytetrafluoroethylene beaker containing 20 g of sliced paraffin wax, and the container was placed in a vacuum oven and maintained at 100°C for 2 hours to obtain an aerogel phase change composite material; the aerogel phase change composite material was taken out of the container, and then the excess phase change material on the surface of the aerogel phase change composite material was wiped off. After being placed at room temperature for 2 hours, a copolymer graphene aerogel phase change composite material (approximately 6 g of paraffin wax was adsorbed) was obtained.
[0128] The phase change temperature and phase change latent heat are close to those of Example 2.
[0129] Comparative Example 1
[0130] Take 91.5g of water and add it to a covered glass bottle. Then add 3.5g of 25% ammonia water and 5g of maleic anhydride-styrene copolymer. After tightening the cap of the glass bottle, place it in an oven and maintain it at 95°C. After four hours, take it out to obtain a uniform 5% mass fraction polymer solution.
[0131] The polymer solution was poured into 6 molds, with 15 ml of the solution poured into each mold. The molds were placed in a -30°C refrigerator and frozen for 2 hours. The frozen samples were transferred to a freeze dryer (temperature below -30°C, pressure below 10 Pa) and freeze-dried for 72 hours. The resulting water-soluble polymer aerogel was then taken out. The water-soluble polymer aerogel was placed in a constant temperature container and heat treated at 180°C for 2 hours to dehydrate and deaminize to obtain a maleimide-based aerogel.
[0132] Comparative Example 2
[0133] 20 g of sliced paraffin was placed in a 30 ml polytetrafluoroethylene beaker, and the container was placed in a vacuum oven and maintained at 100° C. for 2 hours. The beaker was taken out and allowed to stand at room temperature for 2 hours to obtain a paraffin phase change material (i.e., pure phase change material).
[0134] Test Case
[0135] The ID / IG test results of the aerogels prepared in Example 1 and Examples 6-8 are listed in Table 1, and the leakage conditions of the phase change materials prepared in Example 2, Comparative Example 2 and Example 5 are listed in Table 2; the DSC curves and glass transition temperatures Tg of Comparative Example 1 and Example 4 are shown in Figure 1; the thermogravimetric curves of Comparative Example 1 and Example 4 are listed in Figure 2; the temperature curves of the phase change materials of Example 2 and Example 5 under one sun illumination intensity and after the illumination is removed are listed in Figure 3.
[0136] The test results in Figure 3 demonstrate that graphene imparts photothermal conversion capabilities to the phase change material. The graphene-containing aerogel phase change composite material can be heated to above 70°C within 30 minutes and maintained above 50°C for extended periods, demonstrating excellent photothermal conversion performance and enabling efficient utilization of solar energy. The composite phase change material in Example 6 was tested using the same method. Compared to Example 2, the composite phase change material in Example 2 exhibited superior photothermal conversion performance.
[0137] Table 1
[0138] The test results in Table 1 show that the composite aerogel prepared by the present invention has a high reduction efficiency and can reach a high reduction degree in 3 seconds, which is conducive to rapid and large-scale industrial preparation.
[0139] Table 2
[0140] The test results in Table 2 show that aerogel has a good anti-leakage effect on phase change materials and has good application prospects.
[0141] Table 3
[0142] According to the data in Table 3, the loss of latent heat caused by porous aerogel to phase change materials is very small. Phase change composite materials with high latent heat values can be prepared using different organic phase change materials. The addition of aerogel will slightly reduce the melting temperature and solidification temperature of the phase change material.
[0143] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation of the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein. On the contrary, the present invention can be extended to all other methods and applications with the same function.
[0144] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of conflict, the definitions in this specification shall prevail.
[0145] When this specification uses the prefix "well known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, the objects introduced by the prefix include those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become generally recognized in the art to be suitable for similar purposes.
[0146] The endpoints and any values of the ranges disclosed in this application document are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and a separate point value, and the separate point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.
[0147] In the context of this specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
[0148] Moreover, any embodiment described herein may be freely combined with one or more other embodiments described herein, and the technical solutions or technical ideas thus formed shall be deemed as part of the original disclosure or original record of the present invention, and shall not be regarded as new content that has not been disclosed or anticipated herein, unless a person skilled in the art considers that the combination is obviously unreasonable.
Claims
1. A composite aerogel comprising a polymer and graphene, wherein the polymer comprises a structural unit containing a maleic anhydride group and a structural unit containing a maleimide group, wherein the maleic anhydride group is The maleimide group refers to 2. The composite aerogel according to claim 1, characterized in that: Raman spectrum of the composite aerogel surface I D / I G The average value is less than or equal to 1.2, preferably less than or equal to 0.9, more preferably less than or equal to 0.85; and / or, The mass ratio of graphene to polymer is (1:20)-(10:1), preferably (1:10)-(6:1), and more preferably (1:5)-(1:1).
3. The composite aerogel according to claim 1, characterized in that: The polymer in the composite aerogel can be dissolved in ammonia water at 0-150° C. to form a polymer aqueous solution; and / or, The graphene is obtained by reducing graphene oxide, preferably pre-reducing the graphene oxide with a reducing agent and then reducing it with microwaves; more preferably, The reducing agent is selected from at least one of ascorbic acid, gallic acid, sodium borohydride and amino acid.
4. The composite aerogel according to claim 1, wherein: Based on the total molar amount of the structural units containing maleic anhydride groups and the structural units containing maleimide groups as 100%, the molar ratio of the structural units containing maleimide groups in the polymer is 5%-70%, preferably 10%-60%; more preferably 20%-50%.
5. The composite aerogel according to claim 1, wherein: The polymer is derived from a polymer raw material containing one or more structural units containing maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups; preferably, the polymer raw material is a copolymer of a polymerization monomer including one or more polymerization monomers of maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt and an olefin monomer; more preferably, the olefin monomer is at least one of α-methylstyrene, styrene, and isobutylene.
6. The composite aerogel according to any one of claims 1 to 5, characterized in that: The composite aerogel is prepared by reacting a polymer raw material containing one or more structural units selected from maleic anhydride, maleimide, maleic acid and ammonium salt, or maleamic acid and ammonium salt groups with ammonia water in a sealed condition, then mixing the polymer raw material with graphene oxide and a reducing agent, and then subjecting the polymer to pre-freezing, freeze-drying, dehydration and deamination, and reduction treatment.
7. A method for preparing the composite aerogel according to any one of claims 1 to 6, comprising reacting a polymer raw material containing one or more structural units selected from the group consisting of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt with aqueous ammonia in a sealed environment, then mixing the polymer raw material with graphene oxide and a reducing agent, and then pre-freezing, freeze-drying, dehydrating and deammoniating, and reducing the polymer raw material to obtain the composite aerogel.
8. The preparation method according to claim 7, characterized in that The following steps are involved: (1) reacting the polymer raw material with ammonia water in a sealed environment to obtain a polymer aqueous solution; (2) mixing the polymer aqueous solution obtained in step (1) with graphene oxide and a reducing agent to obtain a mixed solution, then pre-freezing the solution, and then freeze-drying the solution to obtain a composite polymer; (3) The composite polymer obtained in step (2) is subjected to heat treatment and then subjected to microwave irradiation to obtain the composite aerogel.
9. The preparation method according to claim 8, characterized in that: In step (1): Based on the total mass of the reaction system as 100%, the mass fraction of the polymer raw material used is 0.1%-30%, preferably 0.5%-10%, more preferably 1%-5%, and based on the mass of ammonia in the ammonia water, the mass fraction of ammonia used is 0.001%-30%, preferably 0.01%-10%, more preferably 0.1%-1%, and the remaining components are water; and / or, The reaction conditions include: The reaction temperature is 0-200° C., preferably 50-150° C., more preferably 80-100° C., and / or the reaction time is 0.01-100 h, preferably 0.5-10 h, more preferably 1-5 h.
10. The preparation method according to claim 8, characterized in that: In step (2): The graphene oxide is derived from a dispersion containing graphene oxide, wherein the concentration of graphene oxide in the dispersion is 1-100 mg / mL, preferably 3-30 mg / mL, more preferably 5-20 mg / mL; and / or, The reducing agent is selected from at least one of ascorbic acid, gallic acid, sodium borohydride, and amino acids; and / or, The mass ratio of the reducing agent to graphene oxide is 1:(0.1-20), preferably 1:(1-3); and / or, During the pre-freezing, the temperatures of the cold sources in all directions of the mixed liquid are the same or different. Preferably, the temperatures of the cold sources in all directions of the mixed liquid are different during the pre-freezing; more preferably, the temperatures of the cold sources in one direction of the mixed liquid are different during the pre-freezing; and / or The freeze-drying conditions include: a temperature of (-10)°C or lower; and / or a vacuum degree of 1000 Pa or lower.
11. The preparation method according to claim 8, characterized in that: In step (3): The heat treatment conditions include: a temperature of 100-300°C, preferably 120-220°C, more preferably 160- 200°C; heat treatment time is 0.1-10 hours, preferably 0.5-3 hours, more preferably 1-2 hours; and / or, The microwave irradiation power is 500-2000W; the microwave irradiation time is 1-10s, preferably 2-7s, and more preferably 3-5s.
12. The preparation method according to any one of claims 7 to 11, characterized in that: The polymer raw material can react with aqueous ammonia to obtain a water-soluble polymer; and / or, The polymer raw material is a copolymer of one or more polymerizable monomers selected from maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt, and an olefin monomer; more preferably, the olefin monomer comprises at least one of α-methylstyrene, styrene, and isobutylene; Preferably, the polymer raw material is at least one of styrene maleic anhydride copolymer and maleic anhydride isobutylene copolymer.
13. A recyclable heat storage phase change composite material comprising a composite aerogel and a phase change material loaded in the composite aerogel; The composite aerogel is the composite aerogel according to any one of claims 1 to 6 or the composite aerogel prepared by the preparation method according to any one of claims 7 to 12.
14. The recyclable heat storage phase change composite material according to claim 13, characterized in that: The mass ratio of the composite aerogel to the phase change material is 1:(0.05-50); and / or, The phase change material is an organic phase change material, preferably a water-soluble phase change material and / or a water-insoluble phase change material, more preferably at least one of polyethylene glycol, lauric acid, stearyl alcohol, and paraffin; and / or, Under the temperature condition that the phase change material is in liquid state, the leakage amount of the phase change material in the recyclable heat storage phase change composite material is less than 10 wt%, preferably less than 5 wt%, and more preferably less than 2 wt%.
15. The method for preparing the recyclable heat storage phase change composite material according to claim 13 or 14, comprising loading the phase change material into the composite aerogel; Preferably, the preparation method of the recyclable heat storage phase change composite material comprises: A composite aerogel obtained by the preparation method according to any one of claims 7 to 12; The phase change material is then loaded into the composite aerogel.
16. Application of the recyclable heat storage phase change composite material according to claim 13 or 14 in the fields of building energy conservation, air conditioning systems, waste heat utilization, and solar energy storage.